Granulomatous Osteonecrosis in Crohn's Disease. (1st December 2000) - Freeman, Hugh J; Owen, David; Millan, Mario
Abstract : A 25-year-old white woman was diagnosed with Crohn's disease involving the small and large intestines. She had a complex clinical course that required treatment with multiple pharmacological agents, including intravenous, oral and rectal corticosteroids. She also received parenteral nutrition with lipid emulsions. Finally, repeated intestinal resections and drainage of perianal abscesses were required. Her disease was complicated by gallstones, urolithiasis and hip pain. After osteonecrosis was diagnosed, joint replacements were performed. Review of the pathological sections from the resected hip, however, resulted in detection of granulomatous inflammation with multinucleated giant cells - the histological 'footprint' of Crohn's disease in the gastrointestinal tract. Because prior specialized perfusion fixation pathological studies of the intestine in Crohn's disease have shown that granulomas are located in the walls of blood vessels, a possible mechanism for the pathogenesis of osteonecrosis in Crohn's disease is chronic microvascular ischemia of bone.